GAMBARAN PENGETAHUAN, SIKAP DAN DUKUNGAN TENAGA KESEHATAN DALAM PELAKSANAAN INISIASI MENYUSU DINI PADA IBU BERSALIN - Mellynda, I Gusti Ayu Trisa; Purnamayanti, Ni Made Dwi; Utarini, Gusti Ayu Eka (ARCHIVE OF COMMUNITY HEALTH, 2024)
Early Breastfeeding Initiation (IMD) is a baby suckling right after birth and the baby is conditioned to be able to independently find the mother's nipple. The purpose of this study was to describe the knowledge, attitudes and support of health workers in implementing IMD in mothers giving birth in the working area of ??the UPTD Puskesmas Klungkung I in 2023. This type of research is descriptive observational. The research was conducted in March-May 2023. The total sample was 34 respondents. The sample collection technique is purposive sampling. Data collection method with a questionnaire.. The validity and reliability tests with a sample of 10 mothers giving birth. The results of the validity test obtained the value of r count > r table, while the results of the reliability test obtained the cronbach alpha value > 0.60. The results showed that 67.6% of mothers had good knowledge, 58.8% had a positive attitude towards the implementation of IMD, 76.5% received support from health workers for the implementation of IMD. Mothers giving birth are expected to consult with birth attendants regarding plans to carry out IMD and health workers are expected to attend training related to IMD. Keywords:  Early Initiation of Breastfeeding, mothers giving birth, knowledge, attitudes, support from health  workers